PolyCO in XRF analysis: Fundamental Parameter Method applied for Japanese Buddhist scroll studies. (November 2021) - Cappuccio, G.; Dabagov, S.B.; Guglielmotti, V.; Hampai, D.; Martini, M.; Mazzuca, C.; Micheli, L.; Redi, M.
Abstract: The quantitative evaluation of chemical elements from X-ray Fluorescence (XRF) analysis still remains a strong hurdle in X-ray Spectrometry, mainly due to significant matrix effects involved in the processes. The Fundamental Parameter Method (FPM) is a valid tool for the calculation of analyte concentration unless the primary source comes from a Synchrotron Radiation facility or the experimental design is based on a confocal layout. The approximation of an infinitely thin sample represents a feasible way to apply the FPM approach along with dedicated X-ray optics implemented in the XRF apparatus to improve the performance of the primary beam (and also of the fluorescence signal reaching the detector). This is routinely available at the XLab Frascati of INFN-LNF thanks to the "Rainbow X-ray" (RXR) facility, the μ XRF station opened to users and optimized for most of X-ray analytical research fields. The basic principle of the station is in the use of various geometrical combinations of polycapillary optics for X-ray beam shaping (focusing/collimation) applied to specially designed laboratory units. The flexible RXR layout allows investigating specimens of the dimensions ranging from several millimeters up to half meter and weighting up to several tens of kilograms with the main advantage of having a detection system able to work separately both at high and low X-ray energies. The aim of the present work is to show the results obtained in quantitative XRF analysis by applying the FPM approach to the RXR experimental layout in a study of the pigments covering two different Japanese scrolls, n.142 838 (also known as Engi Jizo Emakimono ) and n. 142 846, coming from the private Ragusa Collection presently stored at Pigorini Museum in Italy. Highlights: Layout with x-ray tube and polyCO demonstrated for Cultural Heritage. Application of FPM to μXRF studies is a valid tool for quantitative XRF. Use of approximation of "thin" samples resulted successful in pigments study. XRF results confirmed pigments formulation given by historical data.